2001
DOI: 10.1097/00005176-200103000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Early Hepatic Portoenterostomy for Biliary Atresia

Abstract: Although these data suggest that outcomes are worse for patients who undergo the procedure before 30 days of age, they may reflect a difference in the pathogenesis of biliary atresia that brings it to clinical attention earlier and may provide further evidence that biliary atresia is a phenotype for a number of distinct underlying disease processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 11 publications
0
26
2
3
Order By: Relevance
“…Early presentation and surgery has been demonstrated by some to be a risk factor for poor outcome. 16 In this study, this was observed with respect to patients with BASM who tended to have early diagnosis and worse prognosis; however, it was not confirmed among the other subjects.…”
Section: Discussioncontrasting
confidence: 64%
“…Early presentation and surgery has been demonstrated by some to be a risk factor for poor outcome. 16 In this study, this was observed with respect to patients with BASM who tended to have early diagnosis and worse prognosis; however, it was not confirmed among the other subjects.…”
Section: Discussioncontrasting
confidence: 64%
“…Although many researchers advocated the advantage of early operation [2], some noted an adverse effect of early operation, especially during the first month of life [3]. Regarding the impact of the timing of Kasai operation on long-term outcome, a few reports have been published [4,5]; however, it is still very uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…41 This association implies that a younger patient will have an earlier phase of disease and perhaps a lesser degree of liver injury. However, age alone is not a uniform predictor of outcome as demonstrated by the poor survival with the native liver of a cohort of young infants with biliary atresia after hepatoportoenterostomy, 42 suggesting that other factors influence the clinical course of disease, such as the coexistence of severe cardiovascular disease, cytomegalovirus infection, and the type and extent of liver pathology at diagnosis. Prominent histological findings of inflammation in the liver at diagnosis has been reported to correlate with a poor response to hepatoportoenterostomy.…”
Section: Staging the Disease At Diagnosismentioning
confidence: 99%